Synthesis, Characterization and Study of Liquid Crystalline Behavior of New Compounds Containing Thiazolidin-4-one, 1, 2, 3-Triazole and Benzimidazol Rings - Tareq K. Ibraheem (Journal of Global Pharma Technology, 2018)
All new compounds synthesized by many reactions starting from a product the compounds [I]a,b from reaction of 3-phenylenediamine  or 4-phenylenediamine  with chloroacetyl chloride, then the compounds [I]a,b reacted with potassium thiocyanate to yield compounds [II]a,b. While  the compounds[III]a,b yield from  reacted the compounds [I]a,b with sodium azide then the compounds [III]a,b reacted 1,3-dipolar cycloaddition reaction  with   acrylic acid to give compounds [IV]a,b and the later compounds reacted with phenylene diamine to product benzimidazole  compounds [V]a,b . In addition to synthesized acid chloride compounds [VI]a,b  by reacted the compounds  [IV]a,b with   thionyl chloride .Finally reacted the compounds [VI]a,b with  different aromatic amines to give amide compounds[VII-X]a,b . The synthesized derivatives characterized viamp. , FTIR, 1HNMR in addition to mass spectroscopy .The liquid crystals properties were studied by using polarized optical microscope (POM) and differential scanning calorimetry(DSC).Keywords: liquid crystal; benzimidazol; thiazolidin-4-one.